Transformation of PT. LEN: Change Management, Structure Design, and Organizational Development, and Human Resource Performance Supporting Defense Industry Products - Himawan, Agus; Wastum, Wastum; Anggiani, Sarfilianty (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
LEN Limited company is one of Indonesia's defense industries, that always tries to follow the improvement in order not to be left behind by military technology, based on government policy PP No.5 2022, which appointed PT. LEN is the leader of three government companies and all these companies will be able to support the existence of defense independence and become a company that can compete throughout the global market. However, this condition is facing some constraints (human resources, management, organization) which are handled through the transformation of the organization. This research analyzed the combination of variables that are related to transformation, where novelty is the combination of variables that are more than one or two variables in conducting the transformation. This research implemented a qualitative descriptive method with primary data (interview with PT. LEN officer within the transformation division), and secondary data (PT. LEN documents or other related literation). Research results from the analyzed data show that a combination of existing variables can be used as a strong foundation for PT. LEN transformation to be the leader of government company in a new form as DEFEND ID.